Le paysage comme medium dans l’analyse des jeux d’acteurs territoriaux : expérience dans la vallée du Cher (France) - Lolita Voisin; Sylvie Servain-Courant; Arnaud Fache (Belgeo)
Recently in France, the ecological continuity of rivers has become a preoccupation within the managing organisations that are confronted with the application of the European directive that implies, in some cases, the destruction of structures, among which are dams. In the Cher valley, a tributary of the Loire, a study has been carried out in the framework of an exercise with landscape architecture students (M1 National School of Higher Studies in Nature and Landscape Architecture, Blois, France). It called for a landscape analysis to renew the river stream planning. It implied questioning more specifically the involvement of local stakeholder organisations, notably in the context of territorial conflicts. We have developed an elaborate approach, especially regarding the analysis of the stakeholder system, which gives a new interpretation of the landscape by its actors.